First survey of epidemiology and associated risk factors of Human intestinal parasitic infections among Gonabad residents, northeast of Iran - Salehi, Mitra; Razavi, Saber; khajavian, Nasim; Ghasemzadeh-moghaddam, Hamed; Firouzeh, Nima; Minooeian haghighi , Mohammad Hassan (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To investigate the prevalence of parasitic infections in the human population and identify the related risk factors of Gonabad city, southeast of Khorasan Razavi province, northeastern Iran. METHODOLOGY: This cross-sectional study was performed from March to April 2019 in Gonabad city in Khorasan Razavi province in northeastern Iran. One thousand thirty-eight stool samples were examined using parasitological methods like direct wet-mounting, formalin-ether concentration and Gomori's trichrome staining. Moreover, the socio-demographic data of inhabitants were recorded. All statistical analyses were performed using SPSS software (version 16). Qualitative variables were reported as numbers and percentages. RESULTS: The overall intestinal parasitic infection prevalence was 18.1 %, whereas this value for protozoan agents was 16.7% (95% CI 14.14 to 19) and 1.3% (95% CI 0.7 to 2) for helminth parasites. The highest parasitic agent prevalence belongs to Blastocystis sp (12.4 %), Entamoeba coli (1.8%) and Enterobius vermicularis (1.2%), respectively. Giardia lamblia (1.1%) Entamoeba histolytica /dispar (0.3%), Iodamoeba butschlii (0.3%), Chilomastix mesnili (0.3%), Hymenolepis nana (0.2 %) Dientamoeba fragilis (0.2%) and Trichomonas hominis (0.3%) were other identified parasites. Multivariate logistic regression analysis revealed a significant association of parasitic intestinal infections with factors such as age, residency status and source of drinking water (P<0.05). CONCLUSION: Our findings approved that the protozoan agents have a relatively high prevalence among the studied population. So, it could be severe enough to alarm the entities implementing healthcare services measures for parasitic intestinal infection control.